Prospective study of cancer in patients with hypogammaglobulinaemia. - Kinlen, L; Webster, A; Bird, A; Haile, R; Peto, J; Soothill, J; Thompson, R (1985)
Among 377 patients with primary hypogammaglobulinaemia, mainly common variable immunodeficiency (CVID), 316 patients survived the first 2 years after diagnosis and were the subject of a study of cancer incidence. Among the 220 patients with CVID, there was a 5-fold increase of cancer due mainly to large excesses of stomach cancer (47-fold) and lymphomas (30-fold). The excess of stomach cancer is probably related to the high frequency of achlorhydria in CVID. 3 of the 7 patients with stomach cancer and CVID survived for 5 years or longer.